I hope this image will show through nicely: I've done so far: 1/100 = e^-kt ln (1/100) = ln e^-kt -kt = ln(1/100)/ln e t = ln(1/100)/ln e * -k Am I right? Maybe ln e needs to be cancelled to something? Please help me out here.
Follow Math Help Forum on Facebook and Google+
Originally Posted by Aluminium I hope this image will show through nicely: I've done so far: 1/100 = e^-kt ln (1/100) = ln e^-kt -kt = ln(1/100)/ln e t = ln(1/100)/ln e * -k Am I right? Maybe ln e needs to be cancelled to something? Please help me out here. $\displaystyle \ln(e) = 1$
Originally Posted by Aluminium I hope this image will show through nicely: Do you see that $\displaystyle 1=100e^{-kt}$ is the same as $\displaystyle e^{kt}=100~?$
I don't see that yet
Well: $\displaystyle 1=100\cdot e^{-kt} \Leftrightarrow \frac{1}{100}=e^{-kt} \Leftrightarrow 100=\frac{1}{e^{-kt}} \Leftrightarrow 100=e^{kt}$ Can you solve it now for $\displaystyle t$?
View Tag Cloud